A two-dimensional tin-based perovskite material and its preparation method and application

Through mechanochemical synthesis method, the synthesis process of DJ type two-dimensional layered tin-based perovskite materials is simplified, the types of materials are expanded, and the problems of single types and complex synthesis in the existing technology are solved, so as to achieve environmental protection and economical Mass production.

CN115725293BActive Publication Date: 2025-02-14EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211413417.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-11
Publication Date
2025-02-14
Estimated Expiration
2042-11-11

AI Technical Summary

Technical Problem

The existing DJ type two-dimensional layered tin-based perovskite materials have a single type, cumbersome synthesis process, and are prone to toxic by-products.

Method used

By using mechanochemical synthesis method, different types of 2D tin halide and alkanediamine are prepared by grinding a mixed slurry of tin halide and alkanediamine, then adding hydrogen halogen acid and alcohol, performing a second grinding and evaporating solvents. Material.

Benefits of technology

The diversified preparation of two-dimensional tin-based perovskite materials is achieved, the synthesis steps are simplified, the generation of toxic waste acid liquid is avoided, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115725293B_ABST
    Figure CN115725293B_ABST
Patent Text Reader

Abstract

The present invention discloses a two-dimensional tin-based perovskite material and a preparation method and application thereof. The preparation method of the two-dimensional tin-based perovskite material of the present invention comprises the following steps: (1) subjecting a mixed slurry of tin halide and alkylene diamine to a first grinding to obtain a mixture A; (2) subjecting a mixed slurry comprising mixture A, a hydrohalic acid and an alcohol to a second grinding to obtain a mixture B; (3) volatilizing the solvent in the mixture B to obtain; wherein the molar ratio of the tin halide to the alkylene diamine is 1:(0.5-4); the carbon chain length of the alkylene diamine is C6-C10. The preparation method of the two-dimensional tin-based perovskite material of the present invention is a mechanochemical synthesis method with simple steps, mild conditions, environmental friendliness, convenient operation, and suitable for large-scale synthesis. The preparation method of the two-dimensional tin-based perovskite material of the present invention can be used to prepare different types of two-dimensional tin-based perovskite materials, thereby expanding the types of two-dimensional tin-based perovskite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a two-dimensional tin-based perovskite material and a preparation method and application thereof. Background Art

[0002] The semiconductor materials (such as gallium nitride) commonly used in advanced commercial light-emitting diodes (LEDs) are expensive, which limits the widespread application of LEDs in my country. Perovskite materials, as an emerging semiconductor material, have been widely studied in the fields of solar cells and LEDs because of their excellent properties such as high absorption coefficient, high carrier mobility, and low trap state density. In particular, two-dimensional layered perovskite materials have become the most promising next-generation commercial LED semiconductor materials because of their low cost, good stability, low defect state density, and easy to change their optical properties by changing the number of layers and composition. Among them, lead-free two-dimensional tin-based perovskite materials have attracted widespread attention because they can maintain good photoelectric properties while reducing the harm of lead to the human body and the environment. Compared with RP-type two-dimensional layered perovskites, where the inorganic perovskite layers are connected by weak van der Waals forces between organic cations, DJ-type two-dimensional layered perovskites have better structural stability because their inorganic perovskite layers are connected by hydrogen bonds of organic cations, and are therefore favored by more and more people.

[0003] However, the DJ-type two-dimensional layered tin-based perovskite materials that have been reported to have commercial potential are of a single type and complex to synthesize, and a large amount of waste acid that is harmful to the environment is easily produced during the synthesis process. Expanding the types of DJ-type two-dimensional layered tin-based perovskite materials and finding new, simple and environmentally friendly synthesis methods are the research and development goals for achieving their commercial applications. Summary of the invention

[0004] The present invention provides a two-dimensional tin-based perovskite material and its preparation method and application in order to solve the problems existing in the prior art that the DJ-type two-dimensional layered tin-based perovskite material is single in type, the synthesis process is cumbersome, and toxic byproducts are generated. The preparation method of the two-dimensional tin-based perovskite material described in the present invention is a mechanochemical synthesis method with simple steps, mild conditions, environmental friendliness, convenient operation, and suitable for large-scale synthesis. Different types of two-dimensional tin-based perovskite materials can be prepared by this method, expanding the types of two-dimensional tin-based perovskite materials.

[0005] The present invention mainly adopts the following technical solutions to solve the above technical problems:

[0006] The present invention provides a method for preparing a two-dimensional tin-based perovskite material, comprising the following steps:

[0007] (1) subjecting a mixed slurry comprising tin halide and alkanediamine to a first grinding to obtain a mixture A;

[0008] (2) subjecting the mixed slurry including the mixture A, the hydrohalic acid and the alcohol to a second grinding to obtain a mixture B;

[0009] (3) volatilizing the solvent in the mixture B to obtain;

[0010] Wherein, the molar ratio of the tin halide to the alkane diamine is 1:(0.5-4);

[0011] Wherein, the carbon chain length of the alkanediamine may be C6 to C10.

[0012] In the present invention, in step (1), the molar ratio of the tin halide to the alkanediamine is preferably 1:(0.5-2), such as 1:1, 1:1.5 or 1:2.

[0013] In step (1), the alkanediamine is preferably any one of hexamethylenediamine, octanediamine and decanediamine.

[0014] In step (1), the purity of the alkanediamine is greater than 98%.

[0015] In step (1), the tin halide may be SnBr2. The SnBr2 is preferably in the form of SnBr2 powder, and the purity of the SnBr2 powder is preferably 99.9%.

[0016] In step (1), the first grinding time is preferably 1 to 30 min, such as 5 to 10 min, such as 5 min or 10 min.

[0017] In the present invention, in step (2), the hydrohalic acid may be any one of hydrochloric acid, hydrobromic acid and hydroiodic acid, preferably hydrobromic acid.

[0018] In step (2), the hydrohalic acid may be added in the form of a conventional hydrohalic acid solution in the art, and the hydrohalic acid solution is preferably a hydrohalic acid aqueous solution, such as a hydrobromic acid aqueous solution.

[0019] Wherein, the concentration of the hydrobromic acid aqueous solution is preferably 40 wt.%.

[0020] In step (2), the carbon chain length of the alcohol may be C2-C6, such as isopropanol or 1-butanol, preferably isopropanol.

[0021] Wherein, the purity of the isopropanol is preferably 99.9%.

[0022] In step (2), the volume ratio of the hydrohalic acid to the alcohol is preferably 1:(1-4), preferably 1:(1-2.5), for example 1:1, 1:2 or 1:2.5.

[0023] In step (2), the second grinding time is 1 to 30 min, preferably 10 to 15 min, for example 10 min or 15 min.

[0024] In the present invention, in step (2), the mixed slurry can be prepared by conventional methods in the art, that is, the mixture A, the hydrohalic acid and the alcohol are mixed. Preferably, the mixture A and the hydrohalic acid are first mixed, and then the alcohol is added for mixing.

[0025] In the present invention, in steps (1) and (2), the grinding is performed using conventional operations in the art.

[0026] The grinding is preferably performed using an agate grinding mortar.

[0027] In the present invention, in step (3), the volatilization is preferably carried out in a fume hood.

[0028] The volatilization time is preferably 10 to 120 min, preferably 20 to 40 min, such as 20 min, 30 min or 40 min.

[0029] The volatilization method is preferably static volatilization.

[0030] In a preferred embodiment of the present invention, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps:

[0031] (1) subjecting a mixed slurry including SnBr2 powder and alkanediamine to a first grinding to obtain a mixture A;

[0032] (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B;

[0033] (3) volatilizing the solvent in the mixture B to obtain;

[0034] Wherein, the molar ratio of SnBr2 powder to alkanediamine is 1:(0.5-2);

[0035] The purity of the SnBr2 powder is 99.9%;

[0036] The alkanediamine is any one of hexamethylenediamine, octanediamine and decanediamine;

[0037] The first grinding time is 5 to 10 minutes;

[0038] The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:(1-2.5);

[0039] The second grinding time is 10 to 15 minutes;

[0040] The volatilization method is to place the mixture B in a fume hood;

[0041] The volatilization time is 20 to 40 minutes.

[0042] In a specific embodiment of the present invention, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps:

[0043] (1) performing a first grinding on a mixed slurry comprising SnBr2 powder and hexamethylenediamine to obtain a mixture A;

[0044] (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B;

[0045] (3) volatilizing the solvent in the mixture B to obtain;

[0046] Wherein, the molar ratio of SnBr2 powder to hexamethylenediamine is 1:1;

[0047] The purity of the SnBr2 powder is 99.9%;

[0048] The first grinding time is 10 min;

[0049] The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:2.5;

[0050] The second grinding time is 15min;

[0051] The volatilization method is to place the mixture B in a fume hood;

[0052] The volatilization time is 40 minutes.

[0053] In a specific embodiment of the present invention, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps:

[0054] (1) performing a first grinding on a mixed slurry comprising SnBr2 powder and octanediamine to obtain a mixture A;

[0055] (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B;

[0056] (3) volatilizing the solvent in the mixture B to obtain;

[0057] Wherein, the molar ratio of SnBr2 powder to octanediamine is 1:2;

[0058] The purity of the SnBr2 powder is 99.9%;

[0059] The first grinding time is 10 min;

[0060] The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:1;

[0061] The second grinding time is 10 min;

[0062] The volatilization method is to place the mixture B in a fume hood;

[0063] The volatilization time is 30 minutes.

[0064] In a specific embodiment of the present invention, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps:

[0065] (1) performing a first grinding on a mixed slurry including SnBr2 powder and decanediamine to obtain a mixture A;

[0066] (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B;

[0067] (3) volatilizing the solvent in the mixture B to obtain;

[0068] Wherein, the molar ratio of SnBr2 powder to decanediamine is 1:1.5;

[0069] The purity of the SnBr2 powder is 99.9%;

[0070] The first grinding time is 5 min;

[0071] The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:2;

[0072] The second grinding time is 10 min;

[0073] The volatilization method is to place the mixture B in a fume hood;

[0074] The volatilization time is 20 minutes.

[0075] The present invention also provides a two-dimensional tin-based perovskite material, which is prepared by the preparation method of the two-dimensional tin-based perovskite ore.

[0076] In the present invention, the molecular formula of the two-dimensional tin-based perovskite material is preferably [H3NC n H 2n NH3]SnBr4, where n=6-8, for example (H3NC6H 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 or (H3NC 10 H 20 NH3)SnBr4.

[0077] In the present invention, the two-dimensional tin-based perovskite material is preferably a DJ-type two-dimensional layered tin-based perovskite material.

[0078] The present invention also provides a two-dimensional tin-based perovskite material, whose molecular formula is (H3NC6H 12 NH3)SnBr4 or (H3NC 10 H 20 NH3)SnBr4.

[0079] The present invention also provides an application of the two-dimensional tin-based perovskite material in the field of luminescent materials.

[0080] In the present invention, the application is, for example, application in solar cells or LEDs.

[0081] In the present invention, the application is, for example, application as a semiconductor material in solar cells and LEDs.

[0082] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0083] The reagents and raw materials used in the present invention are commercially available.

[0084] The positive and progressive effects of the present invention are:

[0085] (1) The present invention provides a mechanochemical synthesis method with simple steps, mild conditions, environmental friendliness, convenient operation, and suitability for large-scale synthesis, thereby improving the problems of the prior art in that the synthesis steps are complicated and a large amount of harmful waste acid solution is easily generated.

[0086] (2) The present invention synthesizes (H3NC6H 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 and (H3NC 10 H 20 NH3)SnBr4 three DJ-type two-dimensional layered tin-based perovskite materials, the three two-dimensional tin-based perovskite materials have a photoluminescence efficiency PLQY of 40% to 100% at a wavelength of 320 to 370nm. This type of material has the characteristics of high fluorescence quantum yield, large Stokes shift, tunable spectrum and low toxicity.

[0087] (3) The preparation method of the present invention can be used to prepare (H3NC6H 12 NH3)SnBr4 and (H3NC 10 H 20 NH3)SnBr4, which expands the variety of two-dimensional tin-based perovskite materials and provides the possibility for further realizing the diverse applications of this type of materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] Figure 1 Schematic diagram of the preparation process of Examples 1-3.

[0089] Figure 2 Schematic diagram of the structure of three DJ-type two-dimensional layered tin-based perovskites prepared in Examples 1-3.

[0090] Figure 3 XRD diffraction patterns of three DJ-type two-dimensional layered tin-based perovskites prepared in Examples 1-3 measured under a standard XRD light source.

[0091] Figure 4 This is a SEM scanning electron microscope image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 1 with a scale of 50 μm.

[0092] Figure 5 This is a SEM scanning electron microscope image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 5 with a scale of 20 μm.

[0093] Figure 6 This is a SEM scanning electron microscope image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 6 with a scale of 20 μm.

[0094] Figure 7 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 1.

[0095] Figure 8 This is the fluorescence lifetime decay curve of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 1 under 375nm excitation light.

[0096] Fig. 9 This is a test graph of the absolute fluorescence quantum efficiency of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 1 under 350nm excitation light.

[0097] Fig.10 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 2.

[0098] Fig.11 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 3.

[0099] Fig.12 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 4.

[0100] Fig.13 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 5.

[0101] Fig.14 This is the fluorescence lifetime decay curve of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 5 under 375nm excitation light.

[0102] Fig.15 This is a test graph of the absolute fluorescence quantum efficiency of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 5 under 350nm excitation light.

[0103] Fig.16 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 6.

[0104] Fig.17 This is the fluorescence lifetime decay curve of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 6 under 375nm excitation light.

[0105] Fig.18 This is a test graph of the absolute fluorescence quantum efficiency of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 6 under 350nm excitation light.

[0106] Fig.19 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Example 7.

[0107] Fig. 20 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Comparative Example 1.

[0108] Fig.21 This is the photoluminescence image of the DJ-type two-dimensional layered tin-based perovskite powder prepared in Comparative Example 2. DETAILED DESCRIPTION

[0109] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0110] Example 1

[0111] The preparation process of DJ-type two-dimensional layered tin-based perovskite materials can be found in Figure 1 , which includes the following steps:

[0112] (1) SnBr2 (purity: 99.9%) (0.4 mmol) powder and hexamethylenediamine (0.4 mmol) were mixed in an agate mortar and ground for 10 min to obtain a powder;

[0113] (2) adding hydrobromic acid aqueous solution (concentration 40 wt.%) (0.2 mL) and isopropanol (purity 99.9%) solution (0.5 mL) to the powder of step (1), and continuing grinding for 15 min to obtain a viscous yellow sample;

[0114] (3) The sample obtained in step (2) was placed in a fume hood for 40 min to obtain a solid powder, namely (H3NC6H 12 NH3)SnBr4 (hereinafter referred to as C6).

[0115] Example 2

[0116] Prepare (H3NC6H) by the preparation method of Example 1 12 NH3)SnBr4 material, wherein the grinding time of step (2) is 30min.

[0117] Example 3

[0118] Prepare (H3NC6H) by the preparation method of Example 1 12 NH3)SnBr4 material, wherein the amount of hexamethylenediamine is 0.8mmoL.

[0119] Example 4

[0120] Prepare (H3NC6H) by the preparation method of Example 1 12 NH3)SnBr4 material, wherein the isopropanol solution is 0.8mL.

[0121] Example 5

[0122] (1) SnBr2 (purity: 99.9%) (0.4 mmol) powder and octanediamine (0.8 mmol) were mixed in an agate mortar and ground for 10 min to obtain a powder;

[0123] (2) adding hydrobromic acid aqueous solution (concentration 40 wt.%) (0.5 mL) and isopropanol (purity 99.9%) solution (0.5 mL) to the powder of step (1), and continuing grinding for 10 min to obtain a viscous yellow sample;

[0124] (3) The sample obtained in step (2) was placed in a fume hood for 30 min to obtain a solid powder, namely (H3NC8H 16 NH3)SnBr4 (hereinafter referred to as C8).

[0125] Example 6

[0126] (1) SnBr2 (purity: 99.9%) (0.4 mmol) powder and decanediamine (0.6 mmol) were mixed in an agate mortar and ground for 5 min to obtain a powder;

[0127] (2) adding hydrobromic acid aqueous solution (concentration 40 wt.%) (0.4 mL) and isopropanol (purity 99.9%) solution (0.8 mL) to the powder of step (1), and continuing grinding for 10 min to obtain a viscous yellow sample;

[0128] (3) The sample obtained in step (2) was placed in air for 20 min to obtain a solid powder, namely (H3NC 10 H 20 NH3)SnBr4 (hereinafter referred to as C10).

[0129] Example 7

[0130] Prepare (H3NC6H) by the preparation method of Example 1 12 NH3)SnBr4 material, wherein the amount of hexamethylenediamine is 1.2mmoL.

[0131] Embodiments 8 to 11

[0132] Table 1. Amount of each reagent in Examples 8 to 11

[0133]

[0134] Carry out the following preparation steps according to the amounts of each reagent shown in Table 1:

[0135] The preparation process of DJ-type two-dimensional layered tin-based perovskite materials can be found in Figure 1 , which includes the following steps:

[0136] (1) SnBr2 (purity: 99.9%) (0.4 mmol) powder and hexamethylenediamine (0.4 mmol) were mixed in an agate mortar and ground for 5 min to obtain a powder;

[0137] (2) adding isopropanol (purity 99.9%) solution (160 μL), hydrobromic acid aqueous solution (concentration 40 wt.%) and HI solution (concentration 57 wt.%) to the powder of step (1) according to the corresponding amounts in Table 1, and continuing grinding for 15 min to obtain a viscous yellow sample;

[0138] (3) The sample obtained in step (2) was placed in a fume hood for 10 min to obtain a product.

[0139] Comparative Example 1

[0140] The (H3NC8H 16 NH3)SnBr4 material, the specific steps are as follows:

[0141] (1) Add stannous oxide (0.1010 g), hydrobromic acid (2.5 mL), n-octylamine (1000 μL), and 15 mL hypophosphorous acid (50 wt.% in water) into a 50 mL beaker at once, and heat and stir in an oil bath. Slowly increase the temperature to dissolve the reactants in the beaker, and continue stirring for 30 min until the solution becomes clear after the temperature reaches a constant 80°C.

[0142] (2) After heating, place the beaker in an ice water bath to cool down, and let it stand for 1 hour. White crystals gradually precipitate, and the crystals obtained by vacuum filtration are (H3NC8H 16 NH3)SnBr4 material

[0143] Effect Example 1

[0144] The (H3NC6H) prepared in Example 1, Example 5 and Example 6 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 and (H3NC 10 H 20 XRD tests were performed on three two-dimensional tin-based perovskite materials: NH3)SnBr4 using a Rigaku MiniFlex desktop X-ray diffractometer. The test results are shown in Figure 3 shown. Figure 2 (H3NC6H) prepared in Example 1, Example 5 and Example 6 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 and (H3NC 10 H 20 Schematic diagram of the structures of three two-dimensional tin-based perovskite materials: NH3)SnBr4.

[0145] Depend on Figure 3 It can be seen that the main growth plane of the two-dimensional tin-based perovskite materials prepared in Example 1, Example 5 and Example 6 is (002).

[0146] Effect Example 2

[0147] The (H3NC6H) prepared in Example 1, Example 5 and Example 6 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 and (H3NC 10 H 20 The SEM test of three two-dimensional tin-based perovskite materials, NH3)SnBr4, was carried out. The SEM model was FEI Verios46, and a copper mesh was used as the support material. The samples were dropped onto the copper mesh and vacuum dried. The test results are shown in Figures 4 to 6 shown.

[0148] Depend on Figure 4 , Figure 5 and Figure 6 It can be seen that the two-dimensional tin-based perovskite materials prepared in Example 1, Example 5 and Example 6 present a two-dimensional lamellar structure.

[0149] Effect Example 3

[0150] The fluorescence performance of the perovskite materials prepared in Examples 1 to 11 and Comparative Example 1 was tested. The fluorescence spectrum was tested using a JobinYvon FluoroLog spectrometer (Horiba); the fluorescence quantum yield was measured using a Newport 819C-IS-5.3; and the fluorescence lifetime decay curve was measured using an Edinburgh LifeSpec II time-correlated single photon counting spectrometer.

[0151] Depend on Figure 7 , Figure 8 and Fig. 9 It can be seen that (H3NC6H prepared in Example 1 12 The NH3)SnBr4 material has an emission peak at 603nm and an excitation wavelength of 340nm. An exponential decay function can be obtained at an excitation wavelength of 375nm and a PL emission wavelength of 620nm, and the fluorescence lifetime decay curve shows a long fluorescence lifetime decay of τ=2.85μs. Its absolute fluorescence quantum efficiency can be obtained at an excitation wavelength of 350nm, which is 95%.

[0152] Depend on Fig.10 , Fig.11 and Fig.12 It can be seen that (H3NC6H 12 The (NH3)SnBr4 material has an emission peak at 607nm and an excitation wavelength of 350nm. 12 The (NH3)SnBr4 material has an emission peak at 602nm and an excitation wavelength of 350nm. 12 NH3)SnBr4 material has an emission peak at 604nm and an excitation wavelength of 350nm.

[0153] Depend on Fig.13 , Fig.14 and Fig.15 It can be seen that (H3NC8H prepared in Example 5 16The NH3)SnBr4 material has an emission peak at 587nm and an excitation wavelength of 340nm. An exponential decay function can be obtained at an excitation wavelength of 375nm and a PL emission wavelength of 620nm, and the fluorescence lifetime decay curve shows a long fluorescence lifetime decay of τ=2.83μs. Its absolute fluorescence quantum efficiency can be obtained at an excitation wavelength of 350nm, which is 70%.

[0154] Depend on Fig.16 , Fig.17 and Fig.18 It can be seen that (H3NC 10 H 20 The NH3)SnBr4 material has an emission peak at 585nm and an excitation wavelength of 340nm. An exponential decay function can be obtained at an excitation wavelength of 375nm and a PL emission wavelength of 620nm, and the fluorescence lifetime decay curve shows a long fluorescence lifetime decay of τ=2.88μs. Its absolute fluorescence quantum efficiency can be obtained at an excitation wavelength of 350nm, which is 53%.

[0155] Depend on Fig.19 It can be seen that (H3NC6H 12 NH3)SnBr4 material has an emission peak at 620nm and an excitation wavelength of 350nm.

[0156] Depend on Fig. 20 It can be seen that the spectrum shows a red shift from 603nm to 636nm as the I content increases, indicating that the spectrum of DJ-type two-dimensional layered tin-based perovskite materials can be regulated by the preparation method.

[0157] Depend on Fig.21 It can be seen that the (H3NC8H 16 The fluorescence quantum yield of NH3)SnBr4 material can reach 90% at the excitation wavelength of 350nm.

[0158] It can be seen from the above that the (H3NC8H 16 NH3)SnBr4 material and (H3NC8H 16 The absolute fluorescence quantum efficiency of the SnBr4 material is only 20% different. In addition, the preparation method of the two-dimensional tin-based perovskite material of the present invention can also prepare (H3NC6H 12 NH3)SnBr4 and (H3NC 10 H 20 NH3)SnBr4 material, and at the excitation wavelength of 350nm, (H3NC6H 12 The absolute fluorescence quantum efficiency of (NH3)SnBr4 material can reach 95%, 10 H20 The absolute fluorescence quantum efficiency of NH3)SnBr4 material can reach 53%.

[0159] The above embodiments are preferred implementations of the invention, but the implementations of the present invention are not limited to the above examples, and any other changes, modifications, substitutions, and combined simplifications that do not deviate from the spirit and principles of the present invention are equivalent.

Claims

1. A method for preparing a two-dimensional tin-based perovskite material, characterized in that: The steps include: (1) subjecting a mixed slurry of tin halide and alkanediamine to a first grinding to obtain a mixture A; (2) subjecting the mixed slurry including the mixture A, the hydrohalic acid and the alcohol to a second grinding to obtain a mixture B; (3) The solvent in the mixture B is evaporated to obtain; Wherein, the molar ratio of the tin halide to the alkane diamine is 1:(0.5-4); Wherein, the carbon chain length of the alkanediamine is C6~C10.

2. The method for preparing a two-dimensional tin-based perovskite material according to claim 1, characterized in that: In step (1), the molar ratio of the tin halide to the alkanediamine is 1:(0.5-2); and / or, the alkanediamine is any one of hexamethylenediamine, octanediamine and decanediamine; and / or, the purity of the alkanediamine is greater than 98%; And / or, the tin halide is SnBr2; And / or, the first grinding time is 1 to 30 min.

3. The method for preparing a two-dimensional tin-based perovskite material according to claim 2, characterized in that: In step (1), the molar ratio of the tin halide to the alkanediamine is 1:1, 1:1.5 or 1:

2.

4. The method for preparing a two-dimensional tin-based perovskite material according to claim 2, characterized in that: The SnBr2 is in the form of SnBr2 powder.

5. The method for preparing a two-dimensional tin-based perovskite material according to claim 4, characterized in that: The purity of the SnBr2 powder is 99.9%.

6. The method for preparing the two-dimensional tin-based perovskite material according to claim 2, characterized in that: The first grinding time is 5 to 10 min.

7. The method for preparing the two-dimensional tin-based perovskite material according to claim 6, characterized in that: The first grinding time is 5 min or 10 min.

8. The method for preparing a two-dimensional tin-based perovskite material according to claim 1, characterized in that: In step (2), the hydrohalic acid is any one of hydrochloric acid, hydrobromic acid and hydroiodic acid; and / or, the hydrohalic acid is added in the form of a hydrohalic acid solution; And / or, the carbon chain length of the alcohol is C2 to C6; And / or, the second grinding time is 1 to 30 min; and / or, the volume ratio of the hydrohalic acid to the alcohol is 1:(1-4); And / or, in step (3), the volatilization time is 10 to 120 min.

9. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: In step (2), the hydrohalic acid is hydrobromic acid.

10. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: The hydrohalic acid solution is a hydrohalic acid aqueous solution.

11. The method for preparing a two-dimensional tin-based perovskite material according to claim 10, characterized in that: The hydrohalic acid solution is a hydrobromic acid aqueous solution.

12. The method for preparing a two-dimensional tin-based perovskite material according to claim 11, characterized in that: The concentration of the hydrobromic acid aqueous solution is 40 wt.%.

13. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: The alcohol is isopropanol or 1-butanol.

14. The method for preparing a two-dimensional tin-based perovskite material according to claim 13, characterized in that: The alcohol is isopropanol.

15. The method for preparing a two-dimensional tin-based perovskite material according to claim 14, characterized in that: The purity of the isopropanol is 99.9%.

16. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: The second grinding time is 10 to 15 min.

17. The method for preparing a two-dimensional tin-based perovskite material according to claim 16, characterized in that: The second grinding time is 10 min or 15 min.

18. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: The volume ratio of the hydrohalic acid to the alcohol is 1:(1-2.5).

19. The method for preparing a two-dimensional tin-based perovskite material according to claim 18, characterized in that: The volume ratio of the hydrohalic acid to the alcohol is 1:1, 1:2 or 1:2.

5.

20. The method for preparing a two-dimensional tin-based perovskite material according to claim 8, characterized in that: In step (3), the volatilization time is 20 to 40 minutes.

21. The method for preparing a two-dimensional tin-based perovskite material according to claim 20, characterized in that: In step (3), the volatilization time is 20 min, 30 min or 40 min.

22. The method for preparing a two-dimensional tin-based perovskite material according to claim 1, characterized in that: In step (2), the mixed slurry is prepared by the following method: mixing the mixture A, hydrohalic acid and alcohol; And / or, in step (3), the volatilization method is static volatilization.

23. The method for preparing a two-dimensional tin-based perovskite material according to claim 22, characterized in that: In step (2), the mixed slurry is prepared by the following method: firstly, the mixture A and the hydrohalic acid are mixed, and then alcohol is added and mixed.

24. The method for preparing a two-dimensional tin-based perovskite material according to claim 1, characterized in that: The steps include: (1) subjecting a mixed slurry comprising SnBr2 powder and alkylenediamine to a first grinding to obtain a mixture A; (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B; (3) The solvent in the mixture B is evaporated to obtain; Wherein, the molar ratio of SnBr2 powder to alkanediamine is 1:(0.5~2); The purity of the SnBr2 powder is 99.9%; The alkanediamine is any one of hexamethylenediamine, octanediamine and decanediamine; The first grinding time is 5 to 10 min; The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:(1-2.5); The second grinding time is 10 to 15 minutes; The volatilization method is to place the mixture B in a fume hood; The volatilization time is 20 to 40 minutes.

25. The method for preparing a two-dimensional tin-based perovskite material according to claim 24, characterized in that: The steps include: (1) subjecting a mixed slurry including SnBr2 powder and hexamethylenediamine to a first grinding to obtain a mixture A; (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B; (3) The solvent in the mixture B is evaporated to obtain; Wherein, the molar ratio of SnBr2 powder to hexamethylenediamine is 1:1; The purity of the SnBr2 powder is 99.9%; The first grinding time is 10 min; The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:2.5; The second grinding time is 15 min; The volatilization method is to place the mixture B in a fume hood; The volatilization time is 40 min; Alternatively, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps: (1) performing a first grinding on a mixed slurry comprising SnBr2 powder and octanediamine to obtain a mixture A; (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B; (3) The solvent in the mixture B is evaporated to obtain; Wherein, the molar ratio of SnBr2 powder to octanediamine is 1:2; The purity of the SnBr2 powder is 99.9%; The first grinding time is 10 min; The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:1; The second grinding time is 10 min; The volatilization method is to place the mixture B in a fume hood; The volatilization time is 30 min; Alternatively, the method for preparing the two-dimensional tin-based perovskite material comprises the following steps: (1) subjecting a mixed slurry including SnBr2 powder and decanediamine to a first grinding to obtain a mixture A; (2) subjecting the mixed slurry including the mixture A, the hydrobromic acid aqueous solution and the isopropanol to a second grinding to obtain a mixture B; (3) The solvent in the mixture B is evaporated to obtain; Wherein, the molar ratio of SnBr2 powder to decanediamine is 1:1.5; The purity of the SnBr2 powder is 99.9%; The first grinding time is 5 min; The volume ratio of the hydrobromic acid aqueous solution to isopropanol is 1:2; The second grinding time is 10 min; The volatilization method is to place the mixture B in a fume hood; The volatilization time is 20 min.

26. A two-dimensional tin-based perovskite material, characterized in that: It is prepared by the preparation method of the two-dimensional tin-based perovskite material according to any one of claims 1 to 25.

27. The two-dimensional tin-based perovskite material according to claim 26, characterized in that The molecular formula of the two-dimensional tin-based perovskite material is [H3NC n H 2n NH3]SnBr4, where n=6~8; And / or, the two-dimensional tin-based perovskite material is a DJ-type two-dimensional layered tin-based perovskite material.

28. The two-dimensional tin-based perovskite material according to claim 26, characterized in that The molecular formula of the two-dimensional tin-based perovskite material is (H3NC6H 12 NH3)SnBr4、(H3NC8H 16 NH3)SnBr4 or (H3NC 10 H 20 NH3)SnBr4.

29. Use of the two-dimensional tin-based perovskite material according to any one of claims 26 to 28 in the field of light-emitting materials.

Citation Information

Patent Citations

  • Organic-inorganic hybrid zero-dimensional non-lead perovskite material and synthesis method thereof

    CN111909696A

  • Tin-based two-dimensional layered perovskite with high fluorescence quantum yield as well as preparation method and application thereof

    CN113322067A